Double-Blind, Placebo-Controlled, Randomized Study Comparing 0.0003% Calcitriol with 0.1% Tacrolimus Ointments for the Treatment of Endemic Pityriasis Alba - Berenice Moreno-Cruz; Bertha Torres-Álvarez; Diana Hernández-Blanco; Juan Pablo Castanedo-Cazares (Hindawi Limited, 2012)
Background. Pityriasis alba (PA) is a frequent cause of consultation in tropical areas due to its chronic course, frequent relapses, and notorious hypopigmented lesions in pediatric dark skin populations. Currently, no treatment is widely accepted. Objective. To assess the efficacy of 0.0003% calcitriol and 0.1% tacrolimus ointments compared with placebo in the treatment of endemic PA. Methods. Twenty-eight children aged 3-17 years with 56 symmetrical lesions and phototype IV-V, were randomly assigned to receive the treatments on target lesions on the face. Improvement was evaluated at baseline and 8 weeks later clinically and by digital quantification of the affected area, colorimetry, and transepidermal water loss (TEWL). Results. Tacrolimus and calcitriol ointments induced a mean improvement of 68%, compared to 44% of placebo. We found an elevated TEWL in PA lesions. In the treated plaques, the reduction of the affected area was associated with improvement of pigmentation and TEWL. Conclusions. Calcitriol and tacrolimus induced similar repigmentation in endemic PA lesions. Melanogenic, anti-inflammatory, and barrier defect restoration properties of these drugs may explain these findings.